Metode Monitoring Resistensi Populasi Aedes aegypti Dengan Penetapan Konsentrasi Diagnostik - Sari, Vicka Kusuma; Tarwotjo, Udi; Hadi, Mochamad (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2018)
Aedes aegypti is the main vector of dengue fever disease. The most effective way to prevent dengue fever is cutting the spreading chain of dengue fever by controlling the vector with using conventional chemical insecticides. The used of insecticide intensively has became the main factor of resistance in Tembalang, then monitoring is needed to determine the change of A. aegypti susceptibility status against the insecticide. The aim of this research is to determine the sensitivity of A. aegypti population from five locations in Tembalang against pyrethroid synthetic insecticide, and to determine the validity of the diagnostic concentration as a method of monitoring resistance A. aegypti population in Tembalang. This research was conducted in Laboratory of Ecology and Biosystematics Department of Biology Faculty of Science and Mathematics, Diponegoro University Semarang. The procedure of this research were: larvae collection (A. aegypti), insect breeding test, sensitivity test including bioassay, determination of diagnostic concentration and validation. The result showed that the susceptibility level of five population was not significantly different since all populations are still susceptible, with the LC50 range between 0,0031-0,0043% and FR range between 1-1,39 (<4). The result of validation test of diagnostic concentration was 0,0038%, valid as a monitoring method of the resistance of A. aegypti population against pyrethroid synthetic insecticide in Tembalang because c2 value of the five population was lower than the c2 table (df = 1; Î± = 0,05) = 3,84.Â Keywords : A. aegypti, monitoring resistance, LC50, diagnostic concentration..